How state-run media shape perceptions: an analysis of the projection of the Rohingya in the Global New Light of Myanmar. (2nd January 2021) - Kironska, Kristina; Peng, Ni-Ni
ABSTRACT: Under the authority of the Burmese military, the Rohingya have long been subjected to discrimination and segregation in systemic attacks linked to their identity. In 2017, the Burmese security forces launched a series of attacks resulting in nearly a million Rohingya refugees fleeing to camps in Bangladesh. What causes the other people in Myanmar to turn a blind eye towards the dire situation of the Rohingya? Using very similar rhetorical devices to those seen in Central Europe in connection to refugees, influential Burmese monks and army officers spread hateful, exclusionary images and commentaries on social media representing Islam as a threat to Buddhism, 'traditional values' and national security. While the vast majority of international media criticize the Burmese government for its actions and present the Rohingya as a persecuted minority, the state-run Global New Light of Myanmar depicts them as a homogenous group of perpetrators threatening national peace and stability. Through the textual analysis of the outputs of this state-run media outlet, light is shed on the ways in which the situation in Rakhine State has been mis-framed by the state.